THERAPY-RELATED MYELOID NEOPLASMS: PREDISPOSITION AND CLONAL EVOLUTION: T-AML predisposition - Fabiani, Emiliano; Falconi, Giulia; Cristiano, Antonio; Hajrullaj, H.; Falconi, Giulia; Leone, Giuseppe; Voso, Maria Teresa (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Therapy-related Myeloid Neoplasm (t-MN) represents one of the worst long-term consequences of cytotoxic therapy for primary tumors and autoimmune disease. Poor survival and refractoriness to current treatment strategies characterize affected patients from a clinical point of view. In our aging societies, where newer therapies and ameliorated cancer management protocols are improving the life expectancy of cancer patients, therapy-related Myeloid Neoplasms are an emerging problem. Although several research groups have contributed to characterizing the main risk factors in t-MN development, the multiplicity of primary tumors, in association with the different therapeutic strategies available and the new drugs in development, make interpreting the current data still complex. The main risk factors involved in t-MN pathogenesis can be subgrouped into patient-specific, inherited, and acquired predispositions. Although t-MN can occur at any age, the risk tends to increase with advancing age, and older patients, characterized by a higher number of comorbidities, are more likely to develop the disease. Thanks to the availability of deep sequencing techniques, germline variants have been reported in 15-20% of t-MN patients, highlighting their role in cancer predisposition. It is becoming increasingly evident that t-MN with driver gene mutations may arise in the background of Clonal Hematopoiesis of Indeterminate Potential (CHIP) under the positive selective pressure of chemo and/or radiation therapies. Although CHIP is generally considered benign, it has been associated with an increased risk of t-MN. In this context, the phenomenon of clonal evolution may be described as a dynamic process of expansion of preexisting clones, with or without acquisition of additional genetic alterations, that, by favoring the proliferation of more aggressive and/or resistant clones, may play a crucial role in the progression from preleukemic states to t-MN.